2009
DOI: 10.1590/s1413-86702009000600010
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nitric oxide and its up/down stream molecules in the immunity against parasitic infections

Abstract: Nitric oxide (NO) is a potent mediator with diverse roles in regulating cellular functions and signaling pathways. The NO synthase (NOS) enzyme family consists of three major isoforms, which convey variety of messages between cells, including signals for vasorelaxation, neurotransmission and cytotoxicity. This family of enzymes are generally classified as neuronal NOS (nNOS), endothelial NOS (eNOS) and inducible NOS (iNOS). Increased levels of NO are induced from iNOS during infection; while eNOS and nNOS may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 122 publications
2
25
0
2
Order By: Relevance
“…57 Activated macrophages produce large amount of NO, a reactive mediator produced via the NADPH-and l-argininedependent enzyme nitric oxide synthase as a defense strategy against infections. 58,59 The role of NO in the host's response to malaria infection has been increasingly investigated. Previous reports have suggested that NO is essential in preventing or moderating the severe manifestations of malaria infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Activated macrophages produce large amount of NO, a reactive mediator produced via the NADPH-and l-argininedependent enzyme nitric oxide synthase as a defense strategy against infections. 58,59 The role of NO in the host's response to malaria infection has been increasingly investigated. Previous reports have suggested that NO is essential in preventing or moderating the severe manifestations of malaria infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NO has also been reported to have direct anti-parasitic activity that can kill P. falciparum in vitro. 17,18,[59][60][61][62] Therefore, enhanced induced NO production in macrophages infected with rBCG vaccine indicating the ability of the rBCG strain to protect against malaria infection.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide formation has been encountered in many parasitic infections including Giardia [30,31]. It is considered as only part of an immunopathological series against infection [32]. The low NO level may be credited to the release of arginine deiminase and flavohemoglobins by Giardia trophozoites which consumes all the local arginine (precursor of nitric acid formation) [33].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously published the detailed applications of NO modulators, time course infected Balb/c mice. Significance of differences (*p<0.05, ***p<0.001) was determined by student's t-test and one-way anova test using Graph Pad Prism software (n = 10 mice/group) and the associated changes in spleen, as well as plasma, brain and liver concentrations of NO in intracellular parasites including plasmodium and Leishmania (Nahrevanian et al, 2007(Nahrevanian et al, , 2009a(Nahrevanian et al, , 2009b(Nahrevanian et al, , 2012Nahrevanian and Dascombe, 2001;Nahrevanian, 2009;Nemati et al, 2013). This is the first application of oral, local and injection forms of L-Arg against Iranian strain L. major MRHO/IR/75/ER.…”
Section: Discussionmentioning
confidence: 99%